2021
DOI: 10.1007/s10482-021-01615-6
|View full text |Cite
|
Sign up to set email alerts
|

Aquisphaera insulae sp. nov., a new member in the family Isosphaeraceae, isolated from the floating island of Loktak lake and emended description of the genus Aquisphaera

Abstract: Strain JC669 T was isolated from a oating island of Loktak lake, Manipur, India and shared highest 16S rRNA gene sequence identity with Aquisphaera giovannonii OJF2 T . The strain is an aerobe, Gram-stainnegative, yellowish orange coloured, non-motile, NaCl intolerant, spherical to oval shaped, grows in single or aggregates and produce structures which appear like fruiting bodies. Strain JC669 T grows well up to pH 9.0, has MK6 as respiratory quinone, C 18:1 ω9c, C 16:0 and C 18:0 as major fatty acids and phos… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…. The two known aquatic species of Aquisphaera have an incomplete nitrification pathway, thereby lacking the gene coding for ammonia monooxygenase [ 85 ]. Russula has acquired an evolutionarily conserved genetic profile for N acquisition and it specializes in ammonium rather than NO 2 uptake [ 86 ].…”
Section: Discussionmentioning
confidence: 99%
“…. The two known aquatic species of Aquisphaera have an incomplete nitrification pathway, thereby lacking the gene coding for ammonia monooxygenase [ 85 ]. Russula has acquired an evolutionarily conserved genetic profile for N acquisition and it specializes in ammonium rather than NO 2 uptake [ 86 ].…”
Section: Discussionmentioning
confidence: 99%
“…The CMFRI is situated in Tamil Nadu in the south-eastern part of India,. At the time of sample collection, the sampling spots had a pH of 7.0-7.5 and a temperature of 22 • C. Algal mat samples were subjected to enrichment and cultivation in a medium [20,24] containing (per litre distilled water; pH 7.0): N-acetylglucosamine, 2.0 g; KH 2 PO 4 , 0.1 g; peptone, 0.1 g; yeast extract, 0.1 g; vitamin solution, 10 mL; Hutner's basal salts, 20 mL, prepared in distilled water. The antibiotics streptomycin, 400 mg/L, ampicillin, 200 mg/L and cycloheximide, 25 mg/L were added to the medium.…”
Section: Habitat and Isolationmentioning
confidence: 99%
“…Recent studies have shown that India harbours a rich planctomycetal diversity which is reflected by the isolation of several axenic cultures from different aquatic and terrestrial habitats [20][21][22][23][24]. In this study, we describe a novel species belonging to the genus Gemmata based on two novel strains that were independently isolated from two distinct and distantly located ecosystems (ca.…”
Section: Introductionmentioning
confidence: 99%
“…The current known diversity of the phylum Planctomycetota is thus still very incomplete. Several isolation efforts in recent years have led to a substantial number of strains to be brought into pure culture and the formal description of more than half of the currently known species [4,14,[32][33][34][35][36][37][38][39][40][41][42][43][44][45][46]. Taxonomic rearrangements within the phylum were also recently made [47].…”
Section: Introductionmentioning
confidence: 99%